Scissors, Embellishment, and Womanhood: The Material Culture of Acadian Sewing to 1755 - Doda, Hilary (Acadiensis, 2022)
Archaeological investigations of four Acadian settlements have revealed a curiously high number of pairs of sewing and embroidery scissors present at the homesteads. This article examines those artifacts and finds that the high ratio of fine-work tools and the decorative nature of many of the examples reveal a cultural interest in embroidery and embellishment, and a connection to changing European conceptions of genteel feminine accomplishment. These status signals read differently in the Acadian settlement context, which may in turn have contributed to outside observers’ impressions of the Acadians as indolent and without respect for the structure of colonial authority.